Understanding the Role of Functional Groups in Polymeric Binder for Electrochemical Carbon Dioxide Reduction on Gold Nanoparticles. (19th September 2018) - Lee, Ji Hoon; Kattel, Shyam; Xie, Zhenhua; Tackett, Brian M.; Wang, Jiajun; Liu, Chang‐Jun; Chen, Jingguang G.
Abstract: Electrochemical CO2 reduction reaction (CO2 RR) is one of the promising strategies for converting CO2 to value‐added chemicals. Gold (Au) catalysts are considered to be the best benchmarking materials for CO2 RR to produce CO. In this work, the role of different functional groups of polymeric binders on CO2 RR over Au catalysts is systematically investigated by combined experimental measurements and density functional theory (DFT) calculations. Especially, it is revealed that the functional groups can play a role in suppressing the undesired hydrogen evolution reaction, the main competing reaction against CO2 RR, thus enabling more catalytic active sites to be available for CO2 RR and enhancing the CO2 RR activity. Consistent with the DFT prediction, fluorine (F)‐containing functional groups in the F‐rich polytetrafluoroethylene binder lead to a high Faradaic efficiency (≈94.7%) of CO production. This study suggests a new strategy by optimizing polymeric binders for the selective CO2 RR. Abstract : Functional groups in polymeric binders are identified to play a prolific role in enhancing electrochemical CO2 reduction reaction (CO2 RR) by modifying the catalyst surface properties. This study reveals the feasibility that a simple binder replacement can improve the electrocatalytic activity and selectivity of CO2 ‐to‐CO against the competing hydrogen evolution reaction without any complex or expensive sample treatment.